Analysis of The Impact of Covid-19 on MSMEs Case Study: Street Vendors (PKL) in Pasar Raya Padang - Rofi Chandra; Muhammad Giatman; Yuliana (Institute of Computer Science (IOCS), 2022)
The COVID-19 pandemic, which is currently being felt by the world's population, has had a lot of impacts, both by the government and even small communities. The real impact of Covid-19 is that it affects economic problems. One of the impacts that has a very big influence is economic problems. Global economic growth is also declining, marked by a declining world GDP of 2%. Indonesia's economy in the future will be very dependent on the process of handling this pandemic. This research explains the current state of MSMEs that are experiencing a recession, and how MSME actors can maintain their activities. The method used in this study is a qualitative approach with the method of interviewing directly with first-party speakers and SWOT analysis. MSMEs are currently very influential during the pandemic in order to stabilize the economy.